Plasma Thrombospondin as an Indicator of Intravascular Platelet Activation in Patients with Vasculitis - McCrohan, M B; Huang, S W; Sleasman, J W; Klein, P A; Kao, K J (Thrombosis and Haemostasis, 1987)
The use of plasma thrombospondin (TSP) concentration was investigated as an indicator of intravascular platelet activation. Patients (n = 20) with diseases that have known vasculitis were included in the study. The range and the mean of plasma TSP concentrations of patients with vasculitis were 117 ng/ml to 6500 ng/ml and 791±1412 ng/ml (mean ± SD); the range and the mean of plasma TSP concentrations of control individuals (n = 33) were 13 ng/ml to 137 ng/ml and 59±29 ng/ml. When plasma TSP concentrations were correlated with plasma concentrations of another platelet activation marker, β-thromboglobulin (P-TG), it was found that the TSP concentration inei eased exponentially as the plasma β-TG level rose. A positive correlation between plasma levels of plasma TSP and serum fibrin degradation products was also observed. The results suggest that platelets are the primary source of plasma TSP in patients with various vasculitis and that plasma TSP can be a better indicator than β-TG to assess intravascular platelet activation due to its longer circulation half life.
Keywords: Plasma thrombospondin; β-thromboglobulin; Platelet; Vasculitis